The British economy in theory and practice - James M. Livingstone (London : Macmillan, 1974)
This book attempts to tilt the balance the other way to discuss current economic and political issues first, and then to consider whether the available theory explains what actually happens.
Includes Index
aia 24/01/2019
Loans
Keywords: British economy; Economic system; Economic growth - British